In Vivo Activation and Pro-Fibrotic Function of NF-κB in Fibroblastic Cells During Pulmonary Inflammation and Fibrosis Induced by Carbon Nanotubes - Dong, Jie; Ma, Qiang (Frontiers in Pharmacology, 2019)
Exposure to insoluble particles in the lung elicits inflammatory responses that eliminate deposited particulates and repair damaged tissue. Overzealous or prolonged responses lead to chronic conditions, such as fibrosis and malignancy, which are frequently progressive and refractory to drug therapy leading to high rates of disability and mortality. The molecular events underlying the progression of lung inflammation to chronic pathology, in particular, the conversion to fibrosis, remain poorly understood. Fibrogenic multi-walled carbon nanotubes (MWCNTs) have been shown to stimulate prominent acute inflammation that evolves into chronic lesions characterized by chronic inflammation, interstitial fibrosis, and granulomas in mouse lungs. In this communication, we examined the in vivo activation of nuclear factor-kB (NF-kB) signaling in fibroblastic cells during the inflammatory and fibrotic progression induced by MWCNTs. Wild-type C57BL/6J male mice were exposed to two fibrogenic MWCNTs (Mitsui XNRI MWNT-7 and long MWCNTs) by pharyngeal aspiration. Both MWCNTs strongly stimulated the nuclear translocation of NF-kB p65 in lung fibroblasts and myofibroblasts during the acute and chronic responses. Phosphorylated NF-kB p65 at Serine 276, a marker of NF-kB activation, was markedly induced by MWCNTs in the nucleus of fibroblastic cells. Moreover, two NF-kB-regulated genes encoding pro-fibrotic mediators, tissue inhibitor of metalloproteinase 1 (TIMP1) and osteopontin (OPN), respectively, were significantly induced in lung fibroblasts and myofibroblasts. These results demonstrate that NF-kB is activated to mediate transactivation of pro-fibrotic genes in fibroblastic cells during pulmonary acute and chronic responses to CNTs, providing a mechanistic framework for analyzing gene regulation in pulmonary fibrotic progression through NF-kB signaling.